Efektivitas Model Pembelajaran Berdiferensiasi untuk Meningkatkan Kemampuan Literasi Sains pada Siswa Sekolah Dasar Kelas V - Hariyanto, Hariyanto; Priawasana, Endra; Halil, Mohamad; Ansori, Mohammad; Wahid, Abdul; suharto, Suharto (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research is to test the effectiveness of differentiated learning models to improve students' science literacy skills. The method used in this research is a quasy experiment with a one group pretest-posttest design that only uses one class and the comparison technique is the pre-test and post-test scores obtained by students. This research was given to 30 grade VI students of SDN Mumbulsari 3 using a sampling technique in the form of purposive sampling. Data collection instruments in the form of the effectiveness of differentiated learning materials were obtained through science literacy ability tests and student response questionnaires. Based on the results of the study, it was found that the students' science literacy ability test showed an increase (gain score) between the pretest and posttest scores of 0.61 which was in the moderate category; besides that most students gave a positive response to the learning material seen from the percentage of interest in learning materials 85.63% (very interested). Based on the analysis of the data obtained, it shows that differentiated learning materials are effective as learning materials to improve students' science literacy skills in the Merdeka Curriculum.